Characterization of in-situ zirconia/mullite composites prepared by sol-gel technique. Issue 3 (3rd July 2021) - Abdallah, Abdu. I.; Sayed, M.; Awaad, M.; Yousif, Adam H. E.; Naga, S.M.
ABSTRACT: The main objective of this study was to investigate the role of zirconia addition to mullite through an in-situ reaction aimed at improving both the mechanical properties and the sinterability behavior. In this work, mullite–zirconia composites were produced using a sol-gel technique. Different amounts of zirconia (0, 10, 15, and 20 wt.%) were added to the mullite, and the calcined gels were sintered at 1550–1700°C for 1 h. The apparent porosity and bulk density of the blank and zirconia/mullite composites were estimated in accordance with ASTM C-20. The phase composition and sample morphology were evaluated via X-ray diffraction (XRD) and scanning electron microscopy analysis (SEM), respectively. Furthermore, the mechanical properties and thermal expansion coefficient (TEC) were also evaluated. The results revealed that the apparent porosity decreased and the density of the zirconia/mullite composites increased when the sintering temperature was increased from 1550 to 1700°C. However, the mechanical properties improved with increasing zirconia content and MZ20 sintered at 1700°C exhibited the maximum bending strength. The TEC results reflected the influence of the composition on the sample TEC. Samples with higher ZrO2 content yielded higher TEC figures than those with lower content.